Building model trains and planes: An autoethnographic investigation of a human occupation. Issue 2 (2nd April 2016) - Pollard, Nick; Carver, Neil
ABSTRACT: This research utilised an autoethnographic method, termed collective autobiography, to explore the nature and meaning of the amateur hobby of building models from childhood to adulthood. Hobbies and leisure activities are areas of human occupation of increasing interest to a variety of disciplines. Although model making may concern the miniature representation of any subject, this paper focuses on the construction of model aircraft kits, trains and their layouts. As a complex, specific human occupation, modelling is found to contribute to personal well-being and, while the occupation may start in childhood, its associated motivations and required skills develop over a life time. The findings also reveal aspects of the nature of the relationship between the modeller, the process of modelling, and the final product. In addition elements of the gendered nature of modelling, its role within father-son relationships, and the accommodation of modelling within shared domestic spaces are brought to light. The modeller is seen to be a creative individual and a consumer. The specific modelling occupations described are recognised as having their origins within the culture of post-war baby boomer Britain, and the socioeconomic and technological environment of that period.